Fluid inclusion study of the unexposed Kentstown Granite, Co. Meath, Ireland - C. O'Reilly; M. Feely; M. P. Holdstock; W. G. O'Keefe (The Institute of Materials, Minerals and Mining, 1905)
A petrographic and microthermometric study of fluid inclusions in the Kentstown Granite, crosscutting quartz (VI) and calcite+quartz (V 2) veins in the granite and calcite+quartz (V 2) veins in the overlying sediments was performed on samples taken from the borehole. Comparisons of the type 1, type 2 and type 3 fluid inclusion populations recorded in the present study with those from other Irish Caledonian granites strongly suggest a similar fluid evolutionary history. Furthermore, the low-temperature CaC12-rich brines (type 5) of this study, which must be syn- to post-Lower Carboniferous in age, have correlatives both in Irish Caledonian granites and in the Lower Carboniferous base-metal deposits of the Irish midlands